Teacher Strategıes In Overcomıng Readıng Dıffıcultıes In Grade 1 Students Of Pombewe Elementary School - Amanda Putri Ramadani; Andi Imrah Dewi; Kadek Hariana; Zulnuraini; Kasmawati (Elementary Teacher Education Program, Majalengka University, 2026)
This study aims to determine teacher strategies for addressing reading difficulties in first-grade students at Pombewõ Elementary School. The study used a qualitative, descriptive approach. Subjects included first-grade homeroom teachers and first-grade students at Pombewõ Elementary School. Data collection techniques included observation, interviews, and documentation. The data obtained were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing.The results showed that students' reading difficulties focused on three main aspects: visual, phonetic, and psychological. In the visual aspect, students had difficulty distinguishing letters with similar shapes and had a poor ability to memorize alphabetic shapes. In the phonetic aspect, students have not yet mastered the relationship between letters and sounds and have difficulty combining syllables. Meanwhile, in the psychological aspect, students demonstrated low self-confidence, shyness, and fear of peer evaluation. To address these issues, teachers implemented various strategies, such as the use of syllable and phonics methods, reading aloud techniques to improve reading fluency, and game-based learning to increase student motivation. The results of the study showed that the strategy was effective in helping students improve their reading skills and supporting the transition process from the spelling stage to fluent reading.